Application of Experimental Method for the Delay Estimation in Cellular Mobile Networks - Brodnevs Deniss; Kutins Aleksandrs (Transport and Telecommunication)
Increasing interest in the application of cellular mobile networks in time-critical applications requires adequate methods for testing or pre-estimating delays in already deployed and operating networks. At the moment, there is no generally accepted approach to the experimental assessment of delays in mobile cellular networks, so usually, experimental evaluations are based on the use of averaged experimental data, which, by itself, does not allow for obtaining a realistic result. This paper proposes a method that allows one to estimate delay parameters in cells without resorting to results averaging. The delays are presented in the form of the distribution of delay parameters of each cell of a whole network, from which it is possible to determine how many cells comply with the proposed requirements in terms of delays. The results, estimated using the proposed method, are for the presence of “good” signal quality and the absence of overloads and failures in the network.